Factors and Barriers Influencing Technology Integration in the Classroom - John Rey Osben Pelila; Queenie Ferdiline L. Bag-ongan; Jendel Lou P. Talania; Geraldine S Wakat (Halu Oleo University, 2022)
This study aimed to determine the factors and barriers influencing technology integration inside the classroom and how teachers integrate technology. The study employed a systematic review of the literature of previous researches. The researchers utilize online databases from Ebscohost and ERIC databases. Through inclusion-exclusion criteria and a guide using PRISMA Flowchart, 46 articles (qualitative – 19; quantitative – 27) were generated and considered eligible and used in the research. Moreover, screened articles were reviewed using the Research Article Findings Grid. Specifically, articles plotted in the grid were analyzed by identifying similarities and differences, regrouped some positive and negative findings of the different authors, and collated and put under each theme. It was noted that personal factors (i.e., teachers' and students' perspectives and attitudes) and professional factors (i.e., tenure, training, workshops) were the main factors affecting technology integration. Barriers like not enough computers, low internet access, malfunction of printers and computers, computer virus attacks, and others were also noted. Regarding how technology is integrated inside the classroom, suggestions, and recommendations like optimizing digital technology's pedagogies, implementing directives to develop